Самхит индуизмнің сөз маржаны ретінде - Кокеева, Д. (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2018)
In the article it is considered the value and meaning the ghosts of the "samhitts" in the Indians philosophy.